Monsters - Windsor-Smith, Barry 1949- (Fantagraphics Books, 2021)
"The year is 1964. Bobby Bailey doesn't realize he is about to fulfill his tragic destiny when he walks into a US Army recruitment office to join up. Close-mouthed, damaged, innocent, trying to forget a past and looking for a future, it turns out that Bailey is the perfect candidate for a secret U.S. government experimental program, an unholy continuation of a genetics program that was discovered in Nazi Germany nearly 20 years earlier in the waning days of World War II. Bailey's only ally and protector, Sergeant McFarland, intervenes, which sets off a chain of cascading events that spin out of everyone's control. As the titular monsters of the title multiply, becoming real and metaphorical, literal and ironic, the story reaches its emotional and moral reckoning"--
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Windsor-Smith, Barry -- 1949-; Ungeheuer; Soldat; Gentechnologie; Experiment; Genetics, Experimental / Comic books, strips, etc / Fiction; Monsters / Comic books, strips, etc / Fiction; Espionage / Comic books, strips, etc / Fiction; United States / Armed Forces / Recruiting, enlistment, etc / Fiction; Génétique expérimentale / Bandes dessinées / Romans, nouvelles, etc; Monstres / Bandes dessinées / Romans, nouvelles, etc; Bandes dessinées d'espionnage / Romans, nouvelles, etc; Recruiting and enlistment; Espionage; Genetics, Experimental; Monsters; United States; Bandes dessinées / États-Unis / 2000-....; Monstruosités; Experimental genetics / Comic books, strips, etc; Monsters / Comic books, strips, etc; Fiction; Science fiction; Comics (Graphic works); Graphic novels; Historical comics; Science fiction comics; Bandes dessinées; Bandes dessinées historiques; Bandes dessinées de science-fiction; Comic